Pengaruh User Generated Content (UGC) dan Price Bundling terhadap Keputusan Pembelian Produk Richeese Factory Cabang Cibinong - Annisa Nuur Aulia; Dedi Junaedi; Rio Kartika Supriyatna (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study examines the influence of User Generated Content and Price Bundling on purchasing decisions at Richeese Factory’s Cibinong branch. A quantitative approach was used, with data collected through questionnaires distributed to 109 respondents. Multiple linear regression analysis revealed that both User Generated Content and Price Bundling have a positive and significant effect, both partially and simultaneously, on consumer purchasing decisions. Keywords: User Generated Content, Price Bundling, Purchasing Decision.